Food Insecurity and Cardiovascular Disease Risk - Liu, Yibin (Curr Atheroscler Rep, 2021)
PURPOSE OF REVIEW: This review examines the current epidemiological evidence for the relationship between levels of food insecurity and cardiovascular disease (CVD) outcomes among US adults > 17 years. RECENT FINDINGS: Review of recent literature revealed that reduced food security was associated with decreased likelihood of good self-reported cardiovascular health and higher odds of reporting CVD-related outcomes such as coronary heart disease, angina, heart attack, peripheral arterial disease, and hypertension. SUMMARY: Existing evidence suggests a compelling association between each level of reduced food security and CVD risk with a particularly strong association between very low food security and CVD risk. Policies and public health-based strategies are needed to identify the most vulnerable subgroups, strengthen and enhance access to food assistance programs, and promote awareness and access to healthful foods and beverages to improve food security, nutrition, and cardiovascular health.